Iowa : the Hawkeye State - Hamilton, John, 1959- (2017)
Presents the history, geography, climate, plants and animals, cities, transportation, natural resources, industry, sports, entertainment, and people of Idaho, as well as general facts about the Hawkeye State.
The Hawkeye State -- Quick facts -- Geography - Climate and weather -- Plants and animals -- History -- Did you know? -- People -- Cities -- Transportation -- Natural resources -- Industry -- Sports -- Entertainment -- Timeline -- Glossary -- Index.
"Established in 1846"--Cover.
Includes index.
Keywords: Geography -- Iowa -- Juvenile literature; Geography; Iowa -- Juvenile literature; Iowa -- History -- Juvenile literature; Iowa; Iowa; History; Juvenile works